Bioanalisis Metabolit Gliklazida Dalam Mikrosom Hati Manusia Dengan Metode HPLC - Suharjono, Suharjono (Majalah Ilmu Kefarmasian, 2008)
Gliclazide (GZ) is oral sulphonylurea-2 generation used for treatment of diabetes mellitus type-2. Gliclazide is metabolized in the smooth endoplasmic reticulum of liver, which can be made in preparation of human liver microsomes. These microsomes rich in cytochrome P450 (CYP450). Major metabolite of GZ in the microsomes are, 7β-OH-GZ, 6α-OHGz, 6β-OH-GZ, and Me-OH-GZ. HPLC method for GZ me-tabolites was done without extraction by organic solvents, but with direct precipita-tion GZ incubation results in the human liver microsomes using perchloric acid. The aim of the study is to determine the level of four GZ metabolites in human liver microsomes by HPLC method. Gliclazide 400 µM were incubated in human liver microsomes using regenerating reagent at 370C for 90 minutes. The reaction were terminated by cooling the incubation tubes at 40C and the addition of 10 µl perchloric acid 70%, then were added 20 µl solution of internal standard of chlopropamide 200 µM, were centrifuged 14,000 rpm for 10 minutes, supernatan taken. Then 200 µl supernatan were added 5 µl of 2 M NaOH, were mixed and centrifuged again at 14,000 rpm for 5 minutes. Then 65 µl supernatant were injected into HPLC column (Beckman), column Ultrasphere ODS 5 µM 4.6 mm x 25 cm, UV detector at 235 nm. HPLC eluent solution was 5mM acetate buffer (pH 4.3)-Acetonitrile (70: 30), with a flow rate of 1.5 ml / min. The retention times of 7β-OH-GZ, 6α-OHGz, 6β-OH-GZ, Me-OH-GZ, chlorpropamide (IS) and Gliclazide were 4.40; 4.58; 5.55; 7.3; 12.30 and 36 minutes (without microsomes) and that with microsomes only 3 metabolites GZ were measured, except metabolite of 6α-OHGz. Linearity, recovery, reproducibility, precision were very good for determining metabolites GZ in human liver microsomes. Bioanalysis by HPLC method for the main metabolites of 7β-OH-GZ, 6β-OH-GZ and Me-OH-GZ were appropriate, because the method were selected, cheap, easy, fast and good validity.